P PENGARUH PENGAWASAN KEDISIPLINAN KERJA TERHADAP PRODUKSI KARET PADA PT. PANTJA SURYA PERDAGANGAN - Rosintan Sipayung (Politeknik Bisnis Indonesia, 2018)
The purpose of this study is to also learn how to influence supervision work discipline of the rubber production at PT. As for the issue of this research is